Invited Paper: Highly Birefringent Nematic Liquid Crystals and Mixtures. Issue 1 (June 2014) - Kula, P.; Dziaduszek, J.; Herman, J.; Dąbrowski, R.
Abstract Highly birefringent liquid crystals have always been desired by many applications in visible, infrared and recently other spectral regions such as THz and GHz as a active medium for various devices fabrication eg. light shutters, shifters, attenuators, filters, electronic lenses, delay lines, antennas, varactors and laser beam steerers. Our own results in the field have been combined with more important ones from literature and have been summarized and reviewed. Special attention will be given to compounds with oligophenyl and tolane based rigid cores for which dual approach of dipol moment generation have been applied (see figure below). <boxed-text content-type="graphic" id="sdtp00028-gra-0001" position="anchor" orientation="portrait"> </boxed-text> For such molecular design the extension of conjugated π electron system leads to high birefringence but simultaneously promotes strongly the presence of smectic phases and increases melting point and enthalpy. Therefore lateral substituents have to be introduced to the rigid core of molecules. The number, volume and position of lateral substituents depends of the length of the rigid core. Molecular engineering leading to compounds with high birefringence Δn, different value of dielectric anisotropy, low viscosity, and a broad temperature range of the nematic phase will be discussed. The properties of broad temperature range nematic mixtures with positive dielectric anisotropy (Δn=0.3‐0.5) will be presented. Additional attention will be given to the development of low losses materials designed for THz and GHz applications.